Predictors of in-hospital mortality in patients requiring transfer to the medical intensive care unit - Huzefa Jibril; Muhammad Azhar; Ainan Arshad; Safia Awan; Syed Ahsan Ali; Muhammed Tariq (Journal of the Pakistan Medical Association)
Objective: To identify the factors associated with higher odds of in-hospital mortality among inpatients requiring transfer to the medical intensive care unit.